POTENTIAL OF MATOA FRUIT EXTRACT (POMETIA PINNATA) AS ANTIOXIDANT SOURCE - Widya Rahmah; Hasyrul Hamzah; Siti Hajar; Sylvan Septian Ressandy; Erlisa Maharani Putri (Universitas Muhammadiyah Magelang, 2021)
Pometia pinnata or commonly known as matoa is a typical plant of Eastern Indonesia or Papua that grows throughout the Papua archipelago. Matoa contains alkaloids, saponins, tannins, flavonoids, phenolic compounds, terpenoids, and vitamins A, C, E which can boost the immune system. The study aims to examine whether the matoa (Pometia pinnata) has acted as a source of antioxidants where one of the functions of the antioxidants themselves is to increase the body's immune system by fighting free radicals. This study uses a narrative review approach, which is a secondary research method that does not have specific guidelines in its preparation (non-systematic review) using data collected assembled with research topics from various electronic and non-electronic libraries. Based on the results of the study using comparisons with other foods such as lime, spirulina, and carrots, it turns out that the fruit and fruit skins of Matoa contain more vitamin C. It is known that the skin of the fruit and matoa fruit contains vitamin C which works as an antioxidant to increase the body's immune system by fighting free radicals. Also, based on several studies, it is known that the extract of the stem and matoa bark obtained an IC50 value of more than 70 ppm where this value is classified as strong antioxidant activity.